Knowledge, attitude, and practice among non-breast cancer women towards breast cancer screening with a focus on economic factors - Yan Zhou (Scientific Reports)
Abstract Although breast cancer incidence and mortality are rising globally and China has a screening programme, participation remains low due to poor awareness and financial barriers. This cross-sectional study aimed to assess the knowledge, attitude, and practice (KAP) of breast cancer screening among 964 non-breast cancer women, averaging 29.79 years old, through web-based questionnaires and face-to-face interviews. The knowledge, attitude and practice scores were 7.04 ± 4.19 (possible range: 0–20), 25.37 ± 6.09 (possible range: 10–50), and 15.07 ± 2.84 (possible range: 0–20), respectively. Key barriers included embarrassment (65.45%), fear of radiation (49.48%), and treatment costs (70.34%). Structural equation modeling indicated that income had a direct effect on both knowledge (β = 0.36, P = 0.010) and attitude (β = 1.34, P < 0.001). The logistic regression analysis found that identifying as “housewife” (OR = 2.87, 95%CI: 1.11–7.37, P = 0.029) and having no medical insurance (OR = 3.19, 95%CI: 1.13–9.04, P = 0.028) were significantly associated with unwillingness to undergo breast cancer screening. In conclusion, this study shows that there is a significant gap in KAP regarding breast cancer screening among women in China, particularly among low-income groups. To improve screening rates, it is crucial to address these barriers, enhance knowledge, and provide better risk assessment resources.